Glycaemic Status of COPD Patients on Long-term Steroid Therapy (Journal of Rangpur Medical College, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is a preventable and treatable disease characterized by persistent airflow limitation that is usually progressive and associated with an enhanced chronic inflammatory response in the airways and the lung to noxious particles or gases. Among the pharmacological therapy, inhaled beta-2 agonist and anticholinergics are the mainstay therapy of COPD along with corticosteroid. Steroid therapy is associated with various potential adverse effects like steroid induced deranged glycemic status. Objective: This study was aimed to assess the glycaemic status of COPD patients on long term steroid therapy. Methods: This cross-sectional observational study was conducted in the department of Medicine, Rangpur Medical College and Hospital, Rangpur, Bangladesh from January 2022 to June 2022. A total of 55 COPD patients were included in the study based on inclusion and exclusion criteria. Detailed information was obtained in each case according to protocol. Complete history was taken either from patient or accompanying attendants. A thorough clinical examination was done. Relevant investigation reports were collected. All the information was recorded according to fixed protocol. Collected data were classified, edited, coded and entered the computer for statistical analysis by using SPSS version 23. Results: Out of 55 COPD patients, the majority (41.8%) patients belonged to age 51-60 years with mean age 55.5±8.3 years. Male patients were predominant 47(85.5%) and male to female ratio was 5.88:1. Most (72.7%) of the patients received inhaled and 15(27.3%) received systemic with or without inhaled corticosteroid. Only 1 (2.5%) patient was found FBS _7.0 mmol/L in inhaled group and 2(13.3%) in systemic with or without inhaled corticosteroid group. One (2.5%) patient was found plasma glucose 2 hours after a 75-gm glucose _11.1 mmol/L in inhaled group and 2(13.3%) in systemic with or without inhaled corticosteroid group. One (2.5%) patient was found HbA1C > 6.5% in inhaled group and 2(13.3%) in systemic with or without inhaled group. The differences were not statistically significant (p>0.05) between two groups. Conclusion: Majority of the patients had normal HbA1c who were taking inhaled corticosteroid than systemic with or without inhaled corticosteroids.J Rang Med Col. September 2024; Vol. 9, No. 2: 27-32